“Happy Together?”: Envisioning the American Family in the Long 1950s - Andrea Carosso (CoSMO, 2018)
As the nuclear, middle-class American family reached its apotheosis in what I call "the Long 1950s", an almost mythical period of post-war national prosperity, it became the bedrock of the Cold War consensus, charged with political and symbolic values that were often at odds with its realities. This paper first analyzes the forces at play in shaping the myth of family as "happy home corporation" in America, which included media pressure, changing social, demographic and economic conditions as well regressive views of gender and sexual roles, especially as emerging from bestselling marriage and child-care manuals. It then looks at the way in which dissenting evidence from those Long 1950s, especially in the area of sexual behaviors as well as juvenile rebellion, showed the American family caught in a state of flux, which was at odds with the imperatives of the Cold War consensus.